Familiarity for Serious Mental Illness in Help-Seeking Adolescents at Clinical High Risk of Psychosis - Poletti, Michele; Azzali, Silvia; Paterlini, Federica; Garlassi, Sara; Scazza, Ilaria; Chiri, Luigi Rocco; Pupo, Simona; Raballo, Andrea; Pelizza, Lorenzo (Frontiers in Psychiatry, 2021)
Aim: Ultrahigh-risk (UHR) individuals have an increased vulnerability to psychosis because of accumulating environmental and/or genetic risk factors. Although original research examined established risk factors for psychosis in the UHR state, these findings are scarce and often contradictory. The aims of this study were (a) to investigate the prevalence of severe mental illness (SMI) in family members of distinct subgroups of adolescents identified through the UHR criteria [i.e., non-UHR vs. UHR vs. first-episode psychosis (FEP)] and (b) to examine any relevant associations of family vulnerability and genetic risk and functioning deterioration (GRFD) syndrome with clinical and psychopathological characteristics in the UHR group. Methods: Adolescents (n = 147) completed an ad hoc sociodemographic/clinical schedule and the Comprehensive Assessment of At-Risk Mental States to investigate the clinical status. Results: More than 60% UHR patients had a family history of SMI, and approximately a third of them had at least a first-degree relative with psychosis or other SMI. A GRFD syndrome was detected in 35% of UHR adolescents. GRFD adolescents showed baseline high levels of positive symptoms (especially non-bizarre ideas) and emotional disturbances (specifically, observed inappropriate affect). Conclusions: Our results confirm the importance of genetic and/or within-family risk factors in UHR adolescents, suggesting the crucial need of their early detection, also within the network of general practitioners, general hospitals, and the other community agencies (e.g., social services and school).